2014
DOI: 10.1142/s0218271815500054
|View full text |Cite
|
Sign up to set email alerts
|

Vector particles tunneling from BTZ black holes

Abstract: In this paper we investigate vector particles' Hawking radiation from a BTZ black hole. By applying the WKB approximation and the Hamilton-Jacobi Ansatz to the Proca equation, we obtain the tunneling spectrum of vector particles. The expected Hawking temperature is recovered

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…which is also equivalent to the Boltzmann factor: exp(−E net /T ) [8,11,26]. From this point on, we can compute the surface temperature of the event horizon of WAdS 3 BH as .…”
Section: Quantum Tunneling Of Vector Particles From Wads3bhsmentioning
confidence: 99%
“…which is also equivalent to the Boltzmann factor: exp(−E net /T ) [8,11,26]. From this point on, we can compute the surface temperature of the event horizon of WAdS 3 BH as .…”
Section: Quantum Tunneling Of Vector Particles From Wads3bhsmentioning
confidence: 99%
“…Moreover, the Hawking temperature of BH increases due to the rotation parameter. Furthermore, our analysis is similar to the analysis for charged scalar and fermion particles tunneling from these BHs [59][60][61][62][63]. The charged scalar and fermion particles radiate through the BHs horizons with the same energy.…”
Section: Discussionmentioning
confidence: 58%
“…From these methods, the Hamilton-Jacobi method, based on quantum tunneling process of a particle, is the most popular method [17][18][19][20][21][22][23][24][25][26][27]. By using the Hamilton-Jacobi approach, Hawking radiations of a number of black holes as quantum tunneling process of a point particle have been investigated in the literature [28][29][30][31][32][33][34][35][36][37][38][39][40]. Recently, it has been also showed that Elko (dark) particles which are spin-1/2 fermions of mass dimension one and dual-helicity eigen spinors of the charge conjugation operator are emitted at the expected Hawking temperature from black holes and strings [39,40].…”
Section: Introductionmentioning
confidence: 99%